The effect of the Barman model on the development of skill performance among students of the Art Institute Beautiful textured perspective (Journal of the College of Basic Education, 2022)
This study aimed to know the effect of the Barman model on developing the skillful performance of students of the Institute of Fine Arts with perspective subject. To achieve the goal of the research, the researcher used the experimental method on a sample of second-grade students from the Institute of Fine Arts, and the research sample consisted of (20) students who were divided into the experimental and control research groups equally. The researcher used a cognitive achievement test (pre and post) and a skill test. And to access the research results, the researcher used a set of (statistical methods, including:The T-test (t-test) for two independent samples. This test was used for equivalence in the research variables, namely (chronological age - previous experience) between the members of the two experimental and control groups. Paragraph difficulty equation: This equation was used to identify the degree of difficulty of achievement test items. Paragraph discrimination equation. This equation was used to find the distinction of achievement test items. Effectiveness of alternatives: It was used to calculate the effectiveness of incorrect (wrong) alternatives for achievement test items. Cooper's equation was used to calculate the percentage of agreement between the two respondents. The Kiodor Richardson equation / 20 is used to calculate the stability factor of the cognitive test items The most important results of the research showed: